The Impact of Audit Committees on the Realization of an Integration Relationship between Internal and External Audit when Conducting Audits. A Study on Public Shareholding Corporations - KHERSIAT, Ola Mohammad (Journal of Advanced Research in Law and Economics; Vol 11 No 2 (2020): JARLE Volume XI Issue 2(48) Spring 2020, 2020)
This study aims to investigate methods of achieving an integrating relationship between internal and external audit when conducting audit procedures in Jordanian public shareholding corporations, as well as investigate the impact of audit committees achieving such a relationship since an effective internal audit effective  the external auditor`s estimations regarding control risks. The study concludes that all aspects of the realization of an integration relation between internal and external audit have achieved a fair ratio exceeding 60%. Spearman test was used to show the nature of the relationship between the internal and external audit. The test results showed that the relationship between these methods is vulnerable in Jordanian public shareholding corporations, and that audit committees have no statistically significant impact on achieving an integrating relationship between internal and external audits  in conducting audit in Jordanian public shareholding corporations, since the ratio of audit committees interpretation (R2) which amounted to (.145) of the dependent variable difference ( achieving an integrating relationship between internal and external audit in conducting audit) is relatively low, and that the P- value derived for this relation amounted to (.615) which is more than (5%) .